Organizational Commitment at a Provincial Department in South Africa - Keolopile D. Motsaathebe; Molefakgotla A. Molefi (Businesses)
This study explores employees’ perceptions of the Office of the Premier in the North West regarding their level of organizational commitment. Using questionnaires to collect qualitative data, a sample of 214 employees, ranging from entry-level to senior management, from the Office of the Premier in the North West Province were gathered. Data were analyzed using SPSS 2011 software. The overall findings show that younger respondents aged 25–34 had an emotional connection to the organization, which aligns with the existing literature. Furthermore, this age group indicated that one of the primary reasons for continuing to work in their department was that leaving would require considerable personal sacrifice, showing that the more committed the employee becomes, the lower the chance of them leaving. Notably, the empirical evidence further reveals that female employees were less likely than male employees to talk openly about their organization. Gender being a factor for employees talking openly about the organization implies that the management must pay attention to gender dynamics across all levels of the organization and ensure that gender representativeness is achieved. This study significantly contributes to the literature on organizational commitment by providing pertinent information regarding organizational commitment based on age, gender, and tenure.